Process route index (PRI) to assess level of explosiveness for inherent safety quantification - A.M., Shariff; C.T., Leong (2009)

(untitled)
The fundamental concept of quantification of inherent safety level is based on the ranking of chemical process routes. Three pioneering inherent safety indices (i.e. PIIS, ISI and i-Safe) are based on this concept and have treated the chemicals in the process system as individual components and not as mixture. These indices lack of ability to reflect the contribution of individual components in the mixture which may affect the quantification of the inherent safety level for process route selection. A new index known as process route index (PRI) is proposed for inherent safety quantification to address the highlighted issues. Level of explosiveness is used for quantification of the inherent safety level for process route selection to illustrate the importance of the individual contribution of the components in the mixture. PRI is developed based on fundamental process parameters that influence the explosion of chemical processes. One of the important criteria for the quantification of the level of explosiveness is to determine the combustibility of the chemicals based on the difference between lower flammability limit (LFL) and upper flammability limit (UFL). The current available indices do not consider the influence of process temperature and pressure on the UFL and LFL. The PRI is developed with the function of temperature and pressure for the quantification of the explosiveness level. The PRI is benchmarked against the published results of the other indices using HYSYS simulation case studies to produce methyl methacrylate acid (MMA) by various process routes. Benchmarking results conclude that PRI is in close agreement with other inherent safety indices and also able to make differentiation between inherent safety level of process routes which were previously indistinguishable. Â© 2008.